Fixel‐based analysis of the effect of amyloid beta on white matter tracts in neurologically normal 70 year olds. (1st February 2022) - Wagen, Aaron Z.; Zarkali, Angeliki; Coath, William; Buchanan, Sarah M.; Keuss, Sarah E.; Keshavan, Ashvini; Lu, Kirsty; James, Sarah‐Naomi; Pavisic, Ivanna M.; Street, Rebecca E.; Parker, Thomas D.; Lane, Christopher A.; et al.
Abstract: Background: Fixel‐based analysis (FBA) of diffusion MRI allows analysis of brain white matter (WM) tracts with greater specificity than voxel‐based approaches, including measures of microstructural fibre density (FD), macrostructural fibre cross section (FC), and representations of crossing fibres. We use FBA to explore early WM changes associated with amyloid‐β (Aβ) prior to manifestations of Alzheimer's disease. We additionally explored global WM changes associated with increased cardiovascular risk. Method: We performed FBA on 233 participants in the Insight 46 birth cohort study, all of whom have been followed prospectively since birth in a single week in 1946, including cardiovascular risk assessment using the Framingham Risk Score (FRS). At age 69‐71 participants underwent cognitive assessment and combined 18 F‐florbetapir PET‐MRI scans on a single scanner. Aβ positive status was defined using a Gaussian mixed model as a standardised uptake value ratio over 0.6103. Using Aβ positive (n=40) and negative (n=193) participants with no major brain disorders and excellent scan quality, we assessed FD and FC, as well as the combined FD and FC (FDC) metric across all white matter fixels. Subsequently we performed a tract‐of‐interest analysis of associations between Aβ and FDC in 13 selected white matter tracts, 7 defined a priori based on Alzheimer's disease mechanisms, and 6 based on results of the global analysis. Result: Aβ positivity was associated with changes in microstructural and macrostructural changes (FD, FC and FDC), throughout the right corticospinal tract inferior to the internal capsule, and microstructurally in the right inferior longitudinal fasciculus. Similar left sided corticospinal changes were seen in FC and FDC only. Increased FRS was associated with FD changes in the right superior longitudinal fasciculus. Tract‐of‐interest analyses showed no significant associations between FDC and Aβ after false discovery correction using the Benjamini‐Hochberg method. Conclusion: We show Aβ associated changes in fixel‐based metrics in the corticospinal tracts, predominantly affecting the right hemisphere. These preliminary results raise the possibility of these fibres being predisposed to damage, perhaps in a length dependent manner, though longitudinal analysis based on further phases of Insight 46 may prove more powerful to detect change at this very early stage.